Geometria e Topologia - Florentino, Carlos (2012)
Editor Convidado: Carlos Florentino Rui Albuquerque, "Geometria dos espaços de gwistor" Ethan Cotterill, "Counting maps from curves to projective space via graph theory" Rosa Sena-Dias, "Spectral theory for toric orbifolds" Pedro Macias Marques, Helena Soares, "Monads on Segre varieties" Leonor Godinho, Silvia Sabatini, "Towards classifying Hamiltonian torus actions with isolated fixed points" Pedro Vaz, "On Jaeger’s HOMFLY-PT expansions, branching rules and link homology: a progress report" Orlando Neto, Pedro C. Silva, "Waldhausen decomposition and Systems of PDEs"